FINAL REDOXIDATION OF COPPER AND BRONZE ALLOYS THERMODYNAMIC AND KINETIC STUDY (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This thesis investigates the final redoxidation of copper and bronze alloys through a thermodynamic and kinetic perspective. Using equilibrium calculations, Ellingham diagrams, and mass transfer modeling, the research evaluates oxygen pickup mechanisms in molten alloys. Results show that reoxidation significantly affects the purity and mechanical properties of alloys.